HUBUNGAN KUALITAS TIDUR TERHADAP PRESTASI AKADEMIK PADA SISWA KELAS X DAN XI DI SMAS BINA SISWA LAUT DENDANG - Idarni Nazara; Muhammad Taufik Daniel Hasibuan (PT. Hasba Edukasi Mandiri, 2025)
Sleep quality is a condition of a person's ability to obtain and maintain quality sleep, sleep quality refers to a state of sleep that produces a fresh and healthy feeling when a person wakes up, high school students (SMA) are individuals who are experiencing adolescence, where at this time adolescents will experience many problems, one of which is the lack of fulfillment of sleep quality which will affect the adolescent education process, especially academic achievement. Academic achievement is a proof of learning success or the ability to learn a person in carrying out his learning activities according to the weight he achieves. Objective: To determine the relationship of sleep quality to academic achievement in class X and XI students at Bina Siswa Laut Dendang Private High School. Methods: This type of research is quantitative with a correlational approach. Sampling using total sampling of 55 respondents. Data analysis using Spearman's rho correlation test. Results: The results of this study indicate that there is a significant relationship between sleep quality and academic achievement in learning with a p-value of 0.001 <0.05 and a correlation coefficient of 0.789. Conclusion: There is a significant relationship between sleep quality and academic achievement in learning and both have a positive relationship where if the quality is good then academic achievement in learning will be good or vice versa.